ELICITING LEARNERS’ MOTIVATION AND ENGAGEMENT IN ONLINE LEARNING: VOICES FROM GRAMMAR CLASS - Marlina, Neni; Sulastri, Fera (Premise: Journal of English Education and Applied Linguistics, 2023)
The Covid-19 pandemic has affected educational institutions forcing them to switch from an offline to an online learning model. Since it is difficult for Indonesian students to adapt their learning methods, this circumstance has affected classroom life in various ways. This circumstance has also impacted the learners' motivation and involvement in learning. The purpose of this qualitative descriptive case study was to examine how learners' online learning experiences during the Covid-19 pandemic were perceived from the perspectives of their learning motivation and participation in grammar lessons, as these two factors significantly impact learners' success in their academic endeavors. The study employed a purposive sampling with 20 English education students who participated in grammar classes at a public university in Tasikmalaya, West Java, Indonesia. Data were collected using open questionnaires. Thematic analysis was used to analyze the data from the opened questionnaires. The thematic analysis revealed that learners encountered numerous difficulties and hindrances when learning grammar online, which affected their motivation and engagement. This result contributes for practitioners to find out the appropriate teaching strategies for online learning, especially in grammar classrooms.